Baixos níveis de atividade física e síndrome metabólica: Estudo transversal com usuarios do sistema publico de saúde Brasileiro - Turi, Bruna Camilo [UNESP]; Codogno, Jamile Sanches [UNESP]; Fernandes, Romulo Araujo [UNESP]; Monteiro, Henrique Luiz [UNESP] (FapUNIFESP (SciELO), 2016)
This study investigated whether low levels of physical activity in different domains is associated with risk factors for the occurrence of metabolic syndrome or metabolic syndrome itself. Habitual physical activity level was assessed among 963 participants, aged 50 years old or more, using Baecke’s questionnaire. Risk factors for metabolic syndrome followed the recommendations of “The IDF Consensus Worldwide Definition of the Metabolic Syndrome”. All the participants were users of the Brazilian Public Healthcare System. The prevalence of metabolic syndrome was 30.9%. Participants with lower levels of physical activity in leisure-time had higher chances of occurrence of diabetes mellitus, hypercholesterolemia and metabolic syndrome. Occurrence of arterial hypertension was associated with lower levels of sports activities. It was found high rates of risk indicators for the occurrence of metabolic syndrome, as well as for diseases alone as hypertension, diabetes mellitus, hypercholesterolemia, and obesity. Lower involvement in physical activity in different domains increases the prevalence of risk factors for metabolic syndrome.
Low levels of physical activity and metabolic syndrome: Cross-sectional study in the Brazilian public health system
Keywords: Epidemiology; Metabolic syndrome X; Motor activity; Unified health system